Pleurotus pulmonarius stalk waste extract supplementation modulates serum proteins level in red hybrid tilapia Oreochromis sp. upon PAMPs challenge - Joo, Jie Ching; Adawiyah Suriza Shuib,; Nazia Abdul Majid,; Norhidayah Mohd Taufek,; Mohd Nazri Ismail,; Noorlidah Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Utilization of functional feeds to enhance fish health and disease resistance has become common practice in aquaculture over the past few decades. This study investigated the effects of hot water extract (HWE)-supplemented feed on serum protein expression in red hybrid tilapia following PAMPs challenge. Fish were fed with a basal or HWE-supplemented diet for 30 days and subsequently injected with lipopolysaccharide (LPS), polyinosinic: polycytidylic acid (poly(I:C)), or PBS (control). Proteomic analysis revealed differential expression of key immune-related proteins like immunoglobulin µ heavy chain and apolipoprotein A-II, which were significantly higher in the HWE-supplemented group upon LPS challenge. On the other hand, C-type lectin domain-containing protein, immunoglobulin µ heavy chain, hemopexin, serotransferrin, α2-HS-glycoprotein-like, inter-alpha trypsin inhibitor heavy chain H3-like, L-rhamnose-binding lectin, and vitellogenin were lower in the HWE-supplemented diet group as compared to the basal diet group post-poly(I:C) challenge, while plasma protease C1 inhibitor and apolipoprotein Eb increased. Functional classifications analysis revealed that most of the DEPs found were involved in the cellular process, biological regulation, metabolic process, and response to stimulus. LC-MS identified bioactive metabolites in HWE, which may contribute to its immunomodulatory effects. These findings suggest that HWE supplementation modulates immune protein expression and enhances disease resilience in tilapia, offering a sustainable strategy for improving aquaculture productivity.